A Critical Analysis of the Supernatural Approach Between Environmental Education and School Ceremonialism - Moh Zulandri; Erwin Zainuddin; Meggi Rahayu; Muh. Rizal; Dewi Rara (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
The Adiwiyata program is one of the strategic policies of the Indonesian government in realizing sustainable environmental education in schools. Since its launch in 2006 by the Ministry of Environment and Forestry (MoEF), the program is designed to instill ecological values through integration into the curriculum, school culture, and citizen participation. However, the implementation in various schools shows a paradox: on the one hand, Adiwiyata succeeds in encouraging increased concern for the environment, but on the other hand, the practice of its implementation is often trapped in ceremonialism. This phenomenon can be seen from the school orientation that emphasizes the achievement of awards, certifications, and competitions rather than the deep internalization of ecological values. This article aims to conduct a critical analysis of the Adiwiyata approach using a literature-based theoretical study method (desk study). The results of the study show that there is a gap between the normative goal of Adiwiyata as an instrument of ecological awareness transformation and the practice of educational bureaucratic ceremonialism that emphasizes the formal aspect. This article offers a reconstruction of the Adiwiyata approach through the integration of ecological curriculum, the formation of a green school culture, and sustainable community participation. Thus, Adiwiyata not only becomes a symbol of administrative success, but actually serves as a transformative and substantial medium of environmental education.